TAMI-25. UPREGULATION OF CREATINE METABOLISM BY MYELOID CELLS RESULTS IN GLIOBLASTOMA PROGRESSION. (12th November 2021) - Rashidi, Aida; Cordero, Alex; Castro, Brandyn; Hou, David; Dapash, Mark; Zhang, Peng; Han, Yu; Lopez-Rosas, Aurora; Chandel, Navdeep; Lesniak, Maciej; Chang, Catalina; Miska, Jason
Abstract: Malignant brain tumors are uniquely immunosuppressive, with a predominant infiltration of immunosuppressive tumor-associated myeloid cells (TAMCs) and a deficit in T-cells unrivaled to any other tumor. This unique tumor microenvironment (TME) promotes resistance to both conventional and immune therapies for this disease. The underlying mechanisms by which TAMCs promote glioblastoma (GBM) progression are not fully understood. We found that TAMCs specifically upregulate de-novo creatine metabolism within GBM using unbiased genetic and metabolic screening. This metabolic phenotype was confirmed in human GBM patients by comparing peripheral versus tumor-infiltrating myeloid cells. Examination of de-novo creatine generation using Carbon 13 arginine flux revealed that TAMCs, but not tumor-infiltrating CD8 + T-cells, can produce creatine. Furthermore, we demonstrate that TAMCs actively secrete de-novo generated creatine into cell cultures. Examination of the single-cell microenvironment of GBM revealed that malignant cells preferentially express the creatine transporter, indicating that TAMC-derived creatine is taken up by GBM. Notably, SLC6A8 is directly upregulated in the context of hypoxia and suggests that creatine uptake is a mechanism to promote survival under hypoxic stress. Indeed, exogenous creatine supplementation promoted both the migration and survival of multiple glioblastoma cell lines in-vitro . Utilizing an established inhibitor of creatine metabolism, β-Guanidinopropionic acid (β -GPA), we found that β -GPA blocks both the migration and survival of glioma cells under hypoxic stress. Lastly, β -GPA also inhibited creatine secretion by TAMCs, showing that creatine blockade can also influence TAMC metabolic phenotype. In the future, we will examine the importance of creatine metabolism on both immune suppression and tumor progression in-vivo . This work provides novel insights into the role of creatine metabolism in GBM and identifies a unique therapeutic avenue for this devastating disease.